Strategy of Technopreneurship Based on Project-Based Learning for Building Students Entrepreneurship Character in the Digital Era - Ismaul Fitroh; Moh. Imron Rosidi (Journal of Education Research, 2026)
Digital transformation requires universities to produce graduates who are not only academically competent but also adaptable and possess technology-based entrepreneurial character. This study aims to analyze technopreneurship learning strategies and the challenges of their implementation in shaping digital entrepreneurial character. The study employs a qualitative approach using the case study method. The research subjects consisted of the course instructor and 20 students. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions, and their validity was tested through triangulation of sources and techniques. The results of the study indicate that project-based learning and experiential learning approaches are effective in fostering students’ creativity, innovation, independence, and willingness to take risks. However, their implementation faces challenges such as varying levels of digital literacy, difficulties integrating historical content into economically valuable products, low self-confidence, and time management issues. Overall, Technopreneurship education contributes to shifting students’ mindset from job seekers to job creators in the era of digital transformation.